Angiolymphoid hyperplasia with eosinophilia: A potential mimic of kimura’s disease - Laila Wahyuningsih; Maria Fransiska Pudjohartono; Hanggoro Tri Rinonce (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare reactive angio-proliferative lesion. ALHE was initially classified as the late stage of Kimura’s disease (KD), although studies later showed that they were two separate clinical entities. Diagnosing ALHE remains a clinical challenge. Here, we report a case of ALHE in a young man and review current literature with an emphasis on how to distinguish ALHE particularly from KD. A 26-year-old man presented with a subcutaneous nodule in right infra-auricular area. Recurrence had occurred after three surgical excisions. Neither enlargement of salivary glands nor lymph nodes were found. Hematological examinations and renal function were normal. The mass was removed surgically. Microscopic examination showed proliferation of vascular channels with accompanying mixed inflammatory infiltrate consisting of lymphocytes, plasma cells, and eosinophils. Based on clinical data and histopathological examination, the patient was diagnosed with ALHE. Several clinical features differ between ALHE and KD, such as gender predilection, hypereosinophilia, IgE levels, and renal involvement. However, clinical features can overlap, so definitive diagnosis relies on histopathological examination. The most important hallmark of ALHE is vascular proliferation with epithelioid endothelial cells. Distinguishing ALHE from KD is important due to the lack of systemic manifestations in ALHE. However, ALHE can be easily mistaken for other diseases due to its rarity. Careful microscopic examination is very important to distinguish ALHE from KD and other mimicking lesions.